Hollow‐fiber liquid‐phase microextraction coupled with miniature capillary electrophoresis for the trace analysis of four aliphatic aldehydes in water samples. Issue 16 (31st July 2015) - Li, Ying; Yi, Fan; Zheng, Yiliang; Wang, Yu; Ye, Jiannong; Chu, Qingcui
<x xml:space="preserve">Abstract</x> An environmentally friendly method for the trace analysis of four aliphatic aldehydes as water disinfection byproducts has been developed based on hollow‐fiber liquid‐phase microextraction followed by miniature capillary electrophoresis with amperometric detection. After derivatization with 2‐thiobarbituric acid, four aliphatic aldehydes (formaldehyde, acetaldehyde, propylaldehyde, and butyraldehyde) became detectable by the amperometric detector. Under the optimum conditions, four aliphatic aldehydes can be well separated from the coexisting interferents as well as their homologs (pentanal, glyoxal, and methyl‐glyoxal), and the limits of detection (S/N = 3) could reach sub‐nanogram‐per‐milliliter level based on hollow‐fiber liquid‐phase microextraction. The proposed method has been applied for the analyses of above four aliphatic aldehydes in different water samples such as drinking water, tap water, and river water, and the average recoveries were in the range of 90–113%, providing an alternative to conventional and microchip capillary electrophoresis approaches.